Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/molecules28010100
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid’s Impact on Growth, Photosynthesis, and Antioxidant Enzyme Activity of Triticum aestivum When Exposed to Salt

Abstract: Recently, the application of salicylic acid (SA) for improving a plant’s resistance to abiotic stresses has increased. A large part of the irrigated land (2.1% out of 19.5%) is severely affected by salinity stress worldwide. In 2020, total production of wheat (Triticum aestivum) was 761 million tons, representing the second most produced cereal after maize; therefore, research on its salinity tolerance is of world concern. Photosynthetic attributes such as net photosynthetic rate (PN), stomatal conductance (gs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…Similarly, soaking wheat seeds for 15 h in 10 and 20 mM SA solutions had a long-term growth-stimulating effect, lasting up to 50 days of development [ 21 ]. Similar to our results, Azeem and co-authors found a growth-stimulating effect of SA on the 28th day of growth for wheat seeds treated with 0.5 mM and 1 mM SA for 12 h [ 24 ], while Alam et al observed a similar effect on the 30th day when seeds were treated in with 0.5 mM SA for 12 h [ 23 ]. The novel aspects of our study include the investigation of the SA-mediated regulation of leaf blade width and its impact on leaf area, the detailed analysis of photosynthetic pigments and antioxidant metabolism, and the evaluation of the field-level impacts of SA pretreatment on wheat productivity and grain quality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, soaking wheat seeds for 15 h in 10 and 20 mM SA solutions had a long-term growth-stimulating effect, lasting up to 50 days of development [ 21 ]. Similar to our results, Azeem and co-authors found a growth-stimulating effect of SA on the 28th day of growth for wheat seeds treated with 0.5 mM and 1 mM SA for 12 h [ 24 ], while Alam et al observed a similar effect on the 30th day when seeds were treated in with 0.5 mM SA for 12 h [ 23 ]. The novel aspects of our study include the investigation of the SA-mediated regulation of leaf blade width and its impact on leaf area, the detailed analysis of photosynthetic pigments and antioxidant metabolism, and the evaluation of the field-level impacts of SA pretreatment on wheat productivity and grain quality.…”
Section: Discussionsupporting
confidence: 91%
“…This increase in photosynthetic pigments improves the efficiency of photosynthetic processes in the leaves [ 32 , 33 , 34 ] and enhances the antioxidant status of the plants [ 34 , 35 ]. In saline soil conditions, photosynthetic pigments were reduced, as observed in our study ( Figure 2 ) and reported in the literature [ 21 , 22 , 23 , 24 ]. However, pretreatment with SA protects the photosynthetic apparatus of wheat leaves from the negative effects of stress-induced oxidative stress and enhances the efficiency of photosynthesis ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…dissipation mechanisms related to the alleviation of oxidative stress, in line with their role in the plant defense response against pathogens and other abiotic stress [11,14,37]. However, although both elicitors induced a similar response at the photochemical level, gas exchange photosynthetic parameters were only improved by SA, which agrees with previous work reporting the enhancement of net photosynthetic rates (A N ), transpiration rates (E), stomatal conductance (g s ) and intercellular CO 2 concentration (Ci) by exogenous application of SA [38][39][40][41][42][43]. This enhancement of the photosynthetic capacity was not associated with higher chlorophyll content (i.e., SPAD index was similar in all treatments; [39]) nor to a differentially higher stomatal density [44][45][46], but with higher rubisco instantaneous carboxylation e ciency (A N /Ci), suggesting that SA stimulated rubisco activity rather than an increase in pigment content [40,47].…”
Section: Discussionsupporting
confidence: 86%
“…SA stimulated the activity of antioxidant enzymes in plants. In response to salt alkali stress, SA mitigated the damage by increasing the levels of chlorophyll, glycine betaine, proline, total phenol, numerous antioxidants, and defense-related enzyme activities (Alam et al, 2022). The adverse effects of salt alkali stress on Xanthium sibiricum Patr.…”
Section: Introductionmentioning
confidence: 99%